Cardiovascular responses to heat stress in chronic heart failure - Cui, Jian (2014)
Clinical reports have suggested that patients with heart diseases may be particularly vulnerable to heat injury. This review examines the effects of heat stress on cardiovascular and autonomic functions in patients with chronic heart failure (CHF). Laboratory investigations have shown that cutaneous vasodilator responses to heating are impaired in patients, whereas activation of skin sympathetic nerve activation is not attenuated in CHF as compared to controls. Attenuated cutaneous vasodilation may increase the risk of a heat related illness when CHF subjects are exposed to hyperthermic conditions.